Criatividade em educação popular: um diálogo com Paulo Freire - Rosas, Agostinho da Silva (2008)
Creativity has been object of interest of researchers in many branches of knowledge. However, it was only since the 1950's, with Jean P. Guilford, that creativity became an important concept related to the human capacity of thinking, deciding and producing. Until that moment, it was associated to imagination, divine myths, madness signs, witchcraft, or even to the particularity of the high intelligence of scholars. Nowadays the new technology, which challenges human capacity of solving problems quickly, is driving the discussion about creativity and creative action to the center of human affairs. In this contribution, creativity was (re)defined as part of the popular education. The start point was to show the existence of a singularity when creativity is related to popular education; and the finish one was to demonstrate that creativity in popular education needs a kind of liberating creativity. To do so, the theoretical diversity of creativity, popular education, the grounds and principles that delimit the mediator instrument of social transformation were discussed. In this context two issues emerged: Creativity with Paulo Freire and Creativity in popular education, extracted from the Associação Nacional de Pós-Graduação e Pesquisa (ANPEd/GT-06). The first one, because it is part of the ideas that led to the origin of popular education; the second one, because of the scientific representativeness as a forum of discussion about education. The way chosen, as an expression of the dialectic method grounded in Marx perspective, followed a triple movement of theoretical construction, stimulated by the interpretation of Limoeiro Cardoso (1990): a) a real (concrete) way to the abstraction; b) the advance in the abstraction field to new abstractions, without disconsidering the focus on the concrete; c) finally, from these abstractions, it is possible to recover the concrete, which may be called a thought concrete. During the research and the final considerations, it is possible to see that creativity does not delimit the political reason of the educational practice by itself, although it demands human work to create the epistemological, theoretical and philosophical limits, which will give the meaning to the relation of men and women with the world, turning the creative action into a more democratic or authoritarian practice. Therefore, it will be both men s and women s actions that will make the creative action more democratic or oppressive. In popular education, the ethical effort which may show solidarity to the human actions and the freedom of the people, needs the liberating creativity.